TRADING IN INFLUENCE AS A CRIME IN INDONESIA CRIMINAL LAW SYSTEM: A JURIDICAL STUDY - Imansyah, Shahrul Kresna; Sumaryanto , Dr. A. Djoko (YURIS: Journal of Court and Justice, 2022)
This research aims to identify whether the rules in Indonesian Corruption Eradication can be applied in the case of influence trading and to determine the prospects for regulating influence trading in the Indonesian Corruption Eradication Law in the future. As a research method, the researchers uses a normative research method based on the antinomy between one law and another. The results of this study can be applied to cases of trafficking under influence, including Article 5, Article 12 letters a and b, Article 11 of the Corruption Eradication Law and related to Article 55 of the Criminal Code (KUHP). However, the application of these articles still has several weaknesses, both from legal subjects and related to objective requirements. both in the formulation of the elements of the article and strict sanctions then they do not conflict with existing regulations. The form of regulation can be set forth in a special regulation on trading in influence, or it can also be reformulated with the existing articles in the Indonesian Corruption Eradication Law or modify the elements of Article 18 UNCAC, 2003 concerning trading in influence so that the regulation does not overlap with the existing regulations. exists then that it deserves to be criminalized. This aims to create legal certainty and justice for the community and prevent the community from falling into the act of trading in influence.